IMPLEMENTASI METODE AHP PADA SELEKSI POHON INDUK UNGGUL KELAPA SAWIT : IMPLEMENTATION OF THE AHP METHOD IN THE SELECTION OF SUPERIOR OIL PALM PARENT TREES - NUSAIBAH WALIATUL AMIROH (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The selection of superior oil palm mother trees is an important stage in producing high-quality seeds and improving plantation productivity. The process of selecting mother trees at PT ASD Bakrie Oil Palm Seed Indonesia is still carried out manually based on observations and assessments by experts, which can lead to subjectivity, inconsistency, and a relatively long decision-making process. This study aims to develop a web-based decision support system using the Analytic Hierarchy Process (AHP) method to support the selection process objectively, systematically, and measurably. The research methods used include observation, interviews, and literature studies. The Analytic Hierarchy Process (AHP) method was implemented through hierarchical structuring, pairwise comparison, matrix normalization, priority weight calculation, consistency testing, and alternative ranking processes. The criteria used consist of Fresh Fruit Bunch (FFB) productivity, Oil Extraction Rate (OER), pest and disease resistance, tree morphology and health, environmental adaptability, and seed price. This study used six superior mother tree alternatives, namely Themba, Spring, Ovane, Supreme, Tanza MR Gano, and Premium. The results showed that the developed system was able to perform automatic calculations and generate recommendations for the best superior mother trees based on the highest ranking values, where the Themba alternative obtained the highest value of 0,303. In addition, the developed system improved efficiency, objectivity, and accuracy in the decision-making process for selecting superior oil palm mother trees.